Emotions and reading: When reading is the best way to improve skills in adolescents - Jiménez-Pérez, Elena del Pilar; de Vicente-Yagüe Jara, María Isabel; León Urrutia, Manuel; García Guirao, Pedro (Frontiers in Psychology, 2023)
In recent years much research on reading competence in different languages has been published in parallel with the interest generated by the results of the PISA and PIRLS reports which were disseminated in the media and which have subsequently garnered the attention of public authorities. Studies that relate reading competence with emotional intelligence, however, are less frequent. This study aims to deepen the relationship between both constructs, using a quasi-experimental longitudinal approach that observes the evolution of 389 high school students in Spain from 16 to 18 years old. Evidence of a direct relationship between reading competence and emotional intelligence was obtained, particularly in the experimental group in which reading habits were stimulated.